Pengobatan Tradisional Warisan Leluhur Masyarakat Kulisusu di Desa Loji, Kecamatan Kulisusu, Kabupaten Buton Utara - Isra, Isra; Jers, La Ode Topo; Keke, Ahmat (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This study aims to explore and describe traditional healing practices as part of efforts to strengthen the health resilience of local communities, as well as to understand the reasons why the Kulisusu people continue to preserve their ancestral medical heritage in Loji Village, Kulisusu District, North Buton Regency. The theoretical framework used in this study includes the medical system theory by Foster and Anderson (1976) and the cultural inheritance theory by Koentjaraningrat (2009). Informants were selected using a purposive sampling technique. Data collection methods included participant observation and in-depth interviews. The findings reveal that 34 types of plants have been passed down through generations and are utilized by the Kulisusu community as traditional medicine. The use of these locally sourced plants reflects a form of health resilience based on local wisdom. The persistence of this tradition is primarily motivated by the community’s strong belief in the effectiveness of traditional healing practices.